Effects of an Abbreviated Obesity Intervention Supported by Mobile Technology: The ENGAGED Randomized Clinical Trial - Spring, Bonnie (Obesity (Silver Spring), 2017)
OBJECTIVES: To determine the effects on weight loss of three abbreviated behavioral weight loss interventions with and without coaching and mobile technology. METHODS: Randomized controlled efficacy study of three six-month weight loss treatments delivered to 96 adults with obesity: 1) self-guided [SELF], 2) standard [STND], or 3) technology-supported [TECH]. STND and TECH received 8 in-person group treatment sessions. SELF and STND used paper diaries to self-monitor diet, activity, and weight; TECH used a smartphone application with social networking features and wireless accelerometer. RESULTS: Weight loss was greater for TECH and STND than SELF at 6 months [−5.7kg (95% CI: −7.2, −4.1) vs. −2.7kg (95% CI: −5.1, −0.3), p<.05]), but not 12 months. TECH and STND did not differ except that more STND (59%) than TECH (34%) achieved ≥5% weight loss at 6 months (P < 0.05). Self-monitoring adherence was greater in TECH than STND (P <0.001), greater in both interventions than SELF (P <0.001), and covaried with weight loss (r(84) = 0.36 − 0.51, P<.001). CONCLUSIONS: Abbreviated behavioral counseling can produce clinically meaningful weight loss regardless of whether self-monitoring is performed on paper or smartphone, but long-term superiority over standard of care self-guided treatment is challenging to maintain.